Exploring the efficacy of Basella alba mucilage towards the encapsulation of the hydrophobic antioxidants for their better performance. (October 2017) - Das, Sreeparna; Alam, Md. Niharul; Batuta, Shaikh; Ahamed, Giassuddin; Fouzder, Chandrani; Kundu, Rakesh; Mandal, Debabrata; Begum, Naznin Ara
Graphical abstract: Highlights: Exploring Basella alba leaf mucilage as a highly efficient encapsulating agent. It enhances the water solubility and bioavailability of hydrophobic antioxidants. Bioactive flavones and polyphenols were encapsulated in the polysaccharide matrix. These encapsulated systems showed high pH and photo stability. Abstract: In the present study, the efficacy of Basella alba L. (commonly known as Indian spinach) mucilage (BAM ) was explored for the first time towards the encapsulation of hydrophobic antioxidants. The hydrophobic antioxidants were encapsulated into theBAM matrix by modified non-solvent precipitation method and the encapsulated systems were fully characterized on the basis of TGA, DLS and SEM data. Interactions between the components ofBAM matrix and the hydrophobic antioxidants are the key factors for the efficient encapsulation process. These interactions were studied with the help of spectroscopic techniques. TheBAM -encapsulated antioxidants showed high pH and photo-stability. Moreover, the hydrophobic antioxidants after their encapsulation in theBAM matrix showed enhanced water solubility and hence, bioactivity in aqueous medium. Thus, BAM may be explored in future as an ideal candidate for the encapsulation and delivery of the hydrophobic bioactive compounds in cellular medium.